2016
DOI: 10.5539/gjhs.v8n9p281
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Effect of Metformin and Acarbose Accompanying Clomiphene on the Successful Ovulation Induction in Infertile Women with Polycystic Ovary Syndrome

Abstract: The aim of this study was to compare the effects of Metformin and Acarbose accompanying Clomiphene on the successful ovulation induction in infertile women with polycystic ovary syndrome. This randomized double blind clinical trial study was performed on 60 women with polycystic ovary syndrome. Women were selected and randomly divided in two control and intervention groups. Intervention group received Acarbose 100 mg/day for 3 months. In the first, second, and third weeks, they received 1 tablet, 2 tablets, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…The 80 RCTs were published between 2000 and 2020 and included (4028 participants both PCOS and control) that met the inclusion criteria and were included in the meta‐analysis. Forty‐two trials 20–61 diagnosed PCOS based on the Rotterdam 2003 criteria, 62 10 trials 35,63–72 used the National Institute of Health 1990 (NIH, NICHD) criteria, one trial 73 used the Androgen Excess Society 2006 (AES) criteria, 74 and no diagnostic criteria were specified for the remainder of the trials (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…The 80 RCTs were published between 2000 and 2020 and included (4028 participants both PCOS and control) that met the inclusion criteria and were included in the meta‐analysis. Forty‐two trials 20–61 diagnosed PCOS based on the Rotterdam 2003 criteria, 62 10 trials 35,63–72 used the National Institute of Health 1990 (NIH, NICHD) criteria, one trial 73 used the Androgen Excess Society 2006 (AES) criteria, 74 and no diagnostic criteria were specified for the remainder of the trials (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that acarbose combined with clomiphene is more effective than metformin in inducing ovulation and reducing body mass index in infertile women with polycystic ovary syndrome. 19 Before treatment, no obvious differences were found in sex hormone levels, glycolipid metabolism or inflammatory factor levels between the two groups (P > 0.05). After treatment, all ex-hormone levels, glycolipid metabolism and inflammatory factor levels were improved in both groups, which were more significant in the observation group compared with the control group (P < 0.05).…”
Section: A H E a D O F P R I N Tmentioning
confidence: 84%
“…The 58 RCTs were published until 2020, of which 35 RCTs (60.3%) 23,25–27,30–35,40,41,44–46,48,49,51–53,57,58,61,67–70,72,74,76,79–81 diagnosed PCOS based on the Rotterdam criteria 2003 85 ; nine (15.5%) RCTs 24,39,43,47,50,55,56,71,73 used the National Institute of Health 1990 (NIH, NICHD) criteria 86 while no diagnostic criteria were given for the rest of the RCTs (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Two (3.4%) RCTs compared orlistat with placebo 31,58 . Three (5.2%) RCTs examined acarbose with metformin 39,67,71 . Two (3.4%) RCTs compared saxagliptin with metformin 33,74 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation